2007
DOI: 10.1007/s00167-007-0376-y
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic removal of juxtaarticular osteoid osteoma of the elbow

Abstract: A case of a 42-year-old male patient with symptomatic juxtaarticular osteoid osteoma of the capitulum humeri is presented. After the clinical diagnosis was confirmed with plain radiographs, bone scan, computer tomography and magnetic resonance imaging, the patient underwent arthroscopic removal of the lesion. A partial synoviectomy was performed first and then the center of the lesion was marked with Kirschner wire using the X-ray monitoring. The marked lesion was transarticularly removed with a motorized shav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…Zupanc et al reported arthroscopic excision of a 42-year-old male patient with symptomatic juxta-articular osteoid osteoma of the capitellum. The removal of the nidus was performed with a motorised shaver which fragmented the lesion and made it unsuitable for histopathological diagnosis 23. In our case, we did not encounter such limitation in our 23-year-old patient.…”
Section: Discussionmentioning
confidence: 75%
“…Zupanc et al reported arthroscopic excision of a 42-year-old male patient with symptomatic juxta-articular osteoid osteoma of the capitellum. The removal of the nidus was performed with a motorised shaver which fragmented the lesion and made it unsuitable for histopathological diagnosis 23. In our case, we did not encounter such limitation in our 23-year-old patient.…”
Section: Discussionmentioning
confidence: 75%
“…Juxta- and intra-articular osteoid osteomas are rare, especially in the elbow joint, and usually present an atypical clinical picture mimicking more common entities such as monoarticular arthritis, epicondylitis, synovial, traumatic, or degenerative joint pain [2, 6, 1016]. The classically described symptoms for the OO are usually altered and may be misleading, especially if the tumour is intra-articular [4].…”
Section: Discussionmentioning
confidence: 99%
“…The classically described symptoms for the OO are usually altered and may be misleading, especially if the tumour is intra-articular [4]. The pain differs from the classical description in that it is described as less severe and the response to salicylates is less effective [2, 6, 10, 11, 14]. The leading symptoms usually compile joint effusion, synovitis, decreased range of motion and contractures [6, 9, 16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations